Same-sex marriage in Maryland: The saliency of religiosity in determining voter support - Hutto, Jonathan W. (Journal for the sociological integration of religion and society, 2015)
During the Maryland 2012 General election, 52% of voters statewide approved Question 6 legalizing same-sex marriage. In an overwhelmingly Democratic state, early polling demonstrated a difference in support between White and Black Democrats with 70% of White Democrats favoring the measure and over half of Black Democrats disapproving. Nevertheless, the final vote tally in majority Black Prince Georges County showed an even split among voters. A review of survey data from the Washington Post will demonstrate the saliency of religiosity, not race, as the primary factor determining voter support for same sex marriage.